Peter Paul and Mary fifty years in music and life - Yarrow, Peter 1938-2025 (A Peter Yarrow book, 2015)
"This book visually tells us the intimate story of Peter, Paul, and Mary and their music, with stirring images that follow their passionate, fifty-year journey to the center of America's heart. The very best of thousands of photographs, many rare and never before published, taken over five decades by some of the world's top photographers, follow them from their earliest performances in the 1960s, when Mary was the most desired, beautiful, and charismatic performer and a new role model for women. Follow the trio as they lead America to discover the passionate soul of folk music. Peter, Paul, and Mary's songs of defiant hope and a certain unmasked innocence are still a powerful part of our American consciousness, and this book reenacts the history of how the trio marked our lives with their indelible stamp of honesty"--